2018
DOI: 10.1007/s10266-018-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue resistances of Hyflex EDM, WaveOne gold, Reciproc blue and 2shape NiTi rotary files in different artificial canals

Abstract: The aim of the present study was to compare the cyclic fatigue resistances of HyFlex EDM (HEDM), WaveOne Gold (WOG), Reciproc Blue (RB), and 2Shape (TS) NiTi systems having different metallurgic properties. HEDM, WOG, RB, and TS instruments were rotated in artificial canals which were made of stainless steel with an inner diameter of 1.5 mm, 45°, and 90° angles of curvatures and a radius of curvature of 5 mm until fracture occurred, and the time to fracture (TTF) was recorded in seconds. Also, number of cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
1
27
0
3
Order By: Relevance
“…The CM-Wire alloy used in the manufacturing of HyFlex CM files might explain their improved fatigue resistance as compared with that of 2Shape TS1 files, which are made of T-Wire alloy, and TruNatomy Prime files, which are produced using a different heat treatment. Özyürek et al [ 31 ] found higher fatigue resistance of HyFlex EDM files with a controlled memory feature as compared with that of 2Shape TS1 files and concluded that the alloy properties might have contributed to these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CM-Wire alloy used in the manufacturing of HyFlex CM files might explain their improved fatigue resistance as compared with that of 2Shape TS1 files, which are made of T-Wire alloy, and TruNatomy Prime files, which are produced using a different heat treatment. Özyürek et al [ 31 ] found higher fatigue resistance of HyFlex EDM files with a controlled memory feature as compared with that of 2Shape TS1 files and concluded that the alloy properties might have contributed to these results.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might explain why the fatigue resistance of the 2Shape TS1 files in the present study was higher than that of the TruNatomy Prime files (not statistically significant). Özyürek et al [ 31 ] reported that 2Shape TS1 files manufactured with a triple helix cross-sectional design exhibited improved fatigue resistance because of their smaller metal mass as compared with that of WaveOne Gold (Dentsply-Sirona) files, which have a rectangular horizontal cross-section. Another study reported that an increase in file size might result in a decrease in fatigue resistance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of nickel-titanium alloy and the use of mechanical instrumentation in endodontics improved the quality of root canal treatment with less time consuming procedures. Unfortunately, with the use of mechanical devices, the intra-operative fracture of an endodontic instrument has become a more common accident due to the increased torsional and cyclical fatigue stresses (1)(2)(3). The application of less stressing movements as such as alternate or reciprocating motion rather than continuous movement, reduced significantly the risk of intracanal leakage of the endodontic instrument (4).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kaval et al 26 have reported that the cyclic fatigue resistance of Hyflex EDM was significantly higher than that of ProTaper Universal (Dentsply Maillefer) and ProTaper Gold (Dentsply Maillefer) files. In another study, Özyürek et al 27 have reported that the cyclic fatigue resistance of Hyflex EDM was significantly higher than the 2Shape TS2 file.…”
Section: Discussionmentioning
confidence: 94%